Entrepreneurial Values and Strategic Management Essays in Management Theory - Coda, V.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
Vittorio Coda's discussion of the goals and purpose of the business enterprise illuminates the long-running debate over the goals of the firm. His conceptualization of the firm and its relationships within society transcends stale arguments over shareholders versus stakeholders by viewing the firm less as an agent of individual interests and more as an engine of social development that unifies the interests of the different participants. In articulating a model of the entrepreneurial firm embedded in a social system and a values system based upon notions of fairness and social responsibility, Coda offers an original approach to interpret the business system. The view of a socially-responsible, entrepreneurial, business sector surfacing in this book offers an attractive alternative to most of the prevailing models of market capitalism that have attracted criticism over the past decades.
Keywords: Small business; Leadership; Entrepreneurship; Management; Small Business; Business Strategy/Leadership.; Entrepreneurship; Management